2017
DOI: 10.3390/en10091435
|View full text |Cite
|
Sign up to set email alerts
|

Subsynchronous Torsional Interaction of Wind Farms with FSIG Wind Turbines Connected to LCC-HVDC Lines

Abstract: Abstract:High-voltage direct current (HVDC) lines with line-commutated converter (LCC) are being increasingly employed to transmit bulk wind power over long distance. However, this may cause the sub-synchronous torsional interaction (SSTI) between the wind farms and the LCC-HVDC system. The SSTI characteristics of wind farms with fixed-speed induction generator (FSIG) wind turbines connected to LCC-HVDC are investigated in this paper. To simplify the calculations, a modular modeling method is proposed for buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Energies 2020, 13, 2612 9 of 27 From Equations (3), (6), (8), (10) and (12), it is possible to define i DC and i DC as a function of the initial conditions and of the external inputs:…”
Section: Small-signal Model Of the Ac/dc Power Conversion Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Energies 2020, 13, 2612 9 of 27 From Equations (3), (6), (8), (10) and (12), it is possible to define i DC and i DC as a function of the initial conditions and of the external inputs:…”
Section: Small-signal Model Of the Ac/dc Power Conversion Stagementioning
confidence: 99%
“…Limited literature has been published about SSTI phenomena in LNG plants [5][6][7][8]. Differently, numerous studies can be found on SSTI for High Voltage Direct Current (HVDC) applications [9][10][11][12][13]. In this context, SSTI is categorized as the evolution of the Sub-Synchronous Resonance (SSR) phenomenon [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The change in topology triggered by equipment switching events causes transient faults induced by short circuit current, which consequently establishes resonant conditions in a power plant. However, wind farms that employ fixed speed induction generator (FSIG) coupled to HVDC lines and are equipped with line-commutated converters are quickly becoming popular in the transmission of large amounts of electrical power over long distances with significant reductions in transient instabilities, especially due to sub-synchronous torsional interaction [71,72]. Recently, a novel technique for detecting several DC fault conditions in a multi-terminal VSC-HVDC scheme was devised in [73] with the use of transient overvoltage with respect to the cable sheath.…”
Section: Hvdc Transient Protection and Improvement Schemementioning
confidence: 99%
“…The equivalent circuits are shown in Figures 3 and 4, and the circuit equation is shown in Equation (2). i d can be seen as direct current:…”
Section: Switch Closure Processmentioning
confidence: 99%
“…In an AC/DC hybrid grid, the interaction between AC and DC and mutual influences between sending and receiving ends changes the system characteristics significantly. Line commutated converter HVDC (LCC-HVDC) has high level of voltage and large transmission capacity and it is the main component of AC/DC power network [1,2].…”
Section: Introductionmentioning
confidence: 99%